The Automated Acquisition of Topic Signatures for Text Summarization - Lin, Chin-Yew; Hovy, Eduard (18th International Conference on Computational Linguistics (COLING'00), 2000)
In order to produce a good summary, one has to identify the most relevant portions of a given text. We describe in this paper a method for automatically training topic signatures[sets of related words, with associated weights, organized around head topics[and illustrate with signatures we created with 6,194 TREC collection texts over 4 selected topics. We describe the possible integration of topic signatures with ontologies and its evaluaton on an automated text summarization system.